Effect of volar angulation of extra-articular distal radius fractures on distal radioulnar joint stability: a biomechanical study. (October 2015) - Bessho, Y.; Nakamura, T.; Nagura, T.; Nishiwaki, M.; Sato, K.; Toyama, Y.
The relationship between increased volar tilt of the distal radius and distal radioulnar joint stability was examined. Distal radioulnar joint stiffness was recorded at 10° intervals from 10° dorsal angulation to 20° of volar angulation from the anatomical position of the radius. Tests were performed with the intact radioulnar ligament and repeated after partial and then complete sectioning of the radioulnar ligament at the ulnar fovea. With the intact radioulnar ligament, distal radioulnar joint stiffness increased significantly at 10° and 20° of volar angulation. Partial sectioning of the radioulnar ligament resulted in an approximate 10% decrease of distal radioulnar joint stiffness compared with the intact state, but distal radioulnar joint stiffness still increased significantly with greater volar tilt. Complete sectioning of the radioulnar ligament significantly decreased distal radioulnar joint stiffness, and increasing the volar tilt did not result in increased distal radioulnar joint stiffness. These results suggest that volar angulation deformities of the distal radius should be corrected to 10° of volar tilt when the triangular fibrocartilage complex is intact. Level of Evidence: N/A